PORTOVELO, PROVINCIA DE EL ORO" PROYECTO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UNA EMPRESA DEDICADA A LA ELABORACIÓN Y COMERCIALIZACIÓN DE UNA BEBIDA DIURÉTICA Y ANTINFLAMATORIA A BASE DE LOS TALLOS Y HOJAS DE LA CAÑA AGRIA (COSTUS SPICATUS) EN LA CIUDAD DE LOJA - Carrión Carrión, Jorge Abraham (2015)
This research work is developed in the city of Loja, taking aim at presenting a proposal for the implementation of a company dedicated to developing and marketing a drink made of sour cane. This project aimed to determine the "feasibility for the implementation of a company dedicated to the development and commercialization of a drink diuretic and anti-inflammatory based on the stems and leaves of the bitter cane (costus spicatus) in the city of Loja", that allows to generate profit to the investor. The technical study were considered the resources required for the activity of the productive unit, such as machinery and equipment, production capacity, engineering of the project, physical distribution, also managed to identify the macro and micro optimal location of the project concluded that the city of Loja, and specifically, in the district Daniel Alvares, it is ideal for the implementation of the project. The legal administrative study determined that there will be 1 Manager, 1 Secretary - Accountant, 1 head of production, 2 workers and 1 seller. In addition, it will be legally constituted as understood by 2 shareholders limited liability company. The financial study the project basically requires an initial investment of $30.332,21 you will find detailed by a total of 12.610,00 fixed assets; deferred assets of 4.112,00 and a working capital of 13.610,21. Financing will be comprised of a 50,76 equity and the 49.24 will be financed by the Banco Nacional de Fomento. Through the table of total costs the total cost for the first year is 155.974,44 and the income is 187.169,33 that dividing fixed costs and variable allowed to establish a balance of 19.76, function of the installed capacity, based on sales of $36.986,96 and based on the production of 48.669,18 products could be established. It could also be established, through the statement of profit and loss this project achieve utilities from the first year that shall be 17.898,07; Similarly flows were calculated for the five years of life, and for the first 18.039,14 for the other years they are all positive. Made flow allowed for the financial evaluation, with their respective financial indicators, whose values are: net present value (VAN) 34.227,73; Rate internal of return (IRR) reaches the 56,52, relationship benefit cost (BC) of 0.20 for every dollar invested; Capital recovery period (PRC) is 1 year 8 months and 5 days; and finally, sensitivity analysis shows that the project supports an increase in the costs of the 11.57 and to a decrease in revenues from the 9.71. The project has all the necessary guarantees to ensure its viability and projected profitability.